2023
DOI: 10.1002/met.2141
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological conditions during periods of low wind speed and insolation in Germany: The role of weather regimes

Abstract: Renewable power generation from wind and solar energy is strongly dependent on the weather. To plan future sustainable energy systems that are robust to weather variability, a better understanding of why and when periods of low wind and solar power output occur is valuable. We call such periods of low wind speed and insolation “Dunkelflauten”, the German word for “dark wind lulls”. In this article, we analyse the meteorological conditions during Dunkelflauten in Germany by applying the concept of weather regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Finally, short-term events, e.g. Dunkelflautes, can pose significant risk to highly renewable energy systems [12,[41][42][43][44]. A 8-day window for CREDI aligns with previous work [33], and is investigated here, see SI section D for additional figures and the top 50 eight-day events.…”
Section: Credimentioning
confidence: 68%
“…Finally, short-term events, e.g. Dunkelflautes, can pose significant risk to highly renewable energy systems [12,[41][42][43][44]. A 8-day window for CREDI aligns with previous work [33], and is investigated here, see SI section D for additional figures and the top 50 eight-day events.…”
Section: Credimentioning
confidence: 68%
“…With increased reliance on variable renewables and balancing via transmission and energy storage, this paradigm breaks down. In particular, the most critical events to system design extend beyond a single hour or day, and identifying such periods no longer depends only on weather data but also power system parameters including storage and transmission [7,20,44,45].…”
Section: Resultsmentioning
confidence: 99%
“…All costs are in 2013 EUR, but derive from model shadow prices, not actual market prices. [19,40,45]. Power systems based on renewables are primarily wind-dependent in the winter, especially in the northern latitudes [47], making them prone to 'wind droughts' .…”
Section: Figurementioning
confidence: 99%
“…In addition, it is important to highlight that understanding the impacts of regimes on surface weather variables is as important as (or even more important than) understanding large‐scale flow situations (Bloomfield et al ., 2021), especially for economic sectors. For example, studies have shown that in winter there is an overproduction of wind power under cyclonic regimes (Grams et al ., 2017), whereas EuBL and GL blocking events are associated with periods of low electricity production by renewable sources (wind power and solar) and high electricity demand that lead to stress on the electricity system (Mockert et al ., 2022; Otero et al ., 2022). In this context, improving the skill for wintertime EuBL is thus crucial for better preparedness for those critical situations.…”
Section: Discussionmentioning
confidence: 99%